A novel mutation in the last exon of ATRX in a patient with alpha-thalassemia myelodysplastic syndrome. - Costa, D; Fisher, C; Miller, K; Pihan, G; Steensma, D; Gibbons, R; Higgs, D (2006)
We describe a patient with acquired alpha-thalassemia myelodysplastic syndrome (ATMDS). A previously healthy 66-year-old man presented with hemoglobin of 9.3 g/dL, mean corpuscular volume 59 fL, and a bone marrow aspirate with increased erythroid precursors and hypolobulated megakaryocytes. Hemoglobin H inclusions were seen in most red cells after 1% brilliant cresyl blue supravital stain of the peripheral blood. At the molecular level, we identified of a novel mutation in the most 3' exon of the ATRX gene (CGA-->TGA substitution in codon 2407) resulting in a premature termination codon (p.R2407X). This case provides further evidence for a link between ATRX mutations and ATMDS, and suggests a possible role for the conserved Q-box element in ATRX function.